Molecular screening of arsenic related genes from an arsenic resistant psychrotolerant - Tepashini Balu, 1994-, author 612592; Shafinaz Shahir supervisor 487417; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Biologi)) - Universiti Teknologi Malaysia, 2017